2021
DOI: 10.3390/cancers13133288
|View full text |Cite
|
Sign up to set email alerts
|

Selective Antitumor Activity of Datelliptium toward Medullary Thyroid Carcinoma by Downregulating RET Transcriptional Activity

Abstract: Medullary thyroid carcinoma (MTC) is a rare aggressive form of thyroid cancer with high rates of metastasis. Sporadic and hereditary MTC are strongly driven by somatic and germline mutations, respectively, in the transmembrane REarranged during Transfection (RET) proto-oncogene, which encodes a receptor tyrosine kinase. Our previous study identified datelliptium as a novel RET transcription inhibitor, which stabilizes the RET G-quadruplex structures and suppresses RET oncogene transcription. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We investigated the influence of adefovir dipivoxil on the three dimensions of growth of TT spheroids in non-adherent, serum-free culture conditions. Adefovir dipivoxil notably diminished the spheroid size over time, with cell death progressing from the periphery inwards to the spheroid core [ 51 ] ( Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the influence of adefovir dipivoxil on the three dimensions of growth of TT spheroids in non-adherent, serum-free culture conditions. Adefovir dipivoxil notably diminished the spheroid size over time, with cell death progressing from the periphery inwards to the spheroid core [ 51 ] ( Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although MZ-CRC1, an MTC cell line with the M918T mutation, appears to be more resistant to adefovir dipivoxil treatment compared to TT cells carrying the C634W mutation ( Figure S1 ), it can be hypothesized that specific genes might be highly overexpressed in the RET M918T mutant but not in the C634W mutant. This overexpression could contribute to the increased resistance of MZ-CRC1 to the treatment [ 11 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Notably, we also found that normal thyroid cells, Nthy-ori-3-1, and hepatocytes cell lines showed significant resistance to adefovir dipivoxil, indicating that this compound is more selective for MTC.…”
Section: Discussionmentioning
confidence: 99%
“…The imidazo[1,2-a]pyridine moiety coupled with a quinoline framework has attracted a great deal of interest recently in medicinal chemistry because it has structural similarity to antiproliferative compounds such as Ellipticine and Datelliptium. 23,24 It is therefore important to develop new methods of synthesis of imidazopyridines coupled quinolines. Pyrido[2 0 ,1 0 :2,3]imidazo [4,5-c]quinoline has been synthesized using a variety of approaches (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%